2012
DOI: 10.2147/phmt.s33387
|View full text |Cite
|
Sign up to set email alerts
|

Overview of respiratory syncytial virus disease in young children

Abstract: Abstract:Respiratory tract illnesses associated with respiratory syncytial virus (RSV) were first reported more than 160 years ago and gained acceptance as a major respiratory pathogen in the late 1950s. Annual epidemics show a seasonal pattern typically beginning in the late fall and ending in early spring, averaging 5 months in length, and varying in time of onset, offset, and duration depending on geographic location. Manifestations of RSV illness primarily involve the upper respiratory tract but can spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The risk of a serious RSV illness in premature infants is increased if they attend a childcare facility or share a dwelling with multiple siblings or other children. Conditions that compromise handling of respiratory tract secretions, such as congenital abnormalities of the airway and severe neuromuscular disease, are also largely believed to increase the risk of a serious RSV disease ( 11 13 ). The parent study reported a more severe course of RSV-related LRTI infection among premature children compared to full-term children ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of a serious RSV illness in premature infants is increased if they attend a childcare facility or share a dwelling with multiple siblings or other children. Conditions that compromise handling of respiratory tract secretions, such as congenital abnormalities of the airway and severe neuromuscular disease, are also largely believed to increase the risk of a serious RSV disease ( 11 13 ). The parent study reported a more severe course of RSV-related LRTI infection among premature children compared to full-term children ( 9 ).…”
Section: Discussionmentioning
confidence: 99%